PENGARUH METODE GUIDED WRITING BERBANTUAN MEDIA REKA CERITA GAMBAR TERHADAP KETERAMPILAN MENULIS KREATIF DI KELAS III SEKOLAH DASAR - Herlambang Isnandar; Yoesrina Novia Vini Syafitri; Rahmatika Layyinah; Muhamad Ilham; Sani Sapitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation steps of the Guided Writing method assisted by picture-sequencing media and its effect on the creative writing skills of third-grade elementary school students. The study was motivated by students' low ability to develop ideas, organize story plots, and apply proper language rules when writing fiction stories. A quantitative approach with a quasi-experimental nonequivalent control group design was employed, involving class III B as the experimental group and class III A as the control group at SDN Cipaku. Data were collected through a creative writing test and a learning-implementation observation sheet, then analyzed using the Mann-Whitney U test. The results showed that the implementation steps consisted of orientation, presentation, structured practice, guided practice, carried out successfully. The pretest results indicated that both classes had equivalent initial abilities (Sig. 0.502), while the posttest results showed a significant improvement in the experimental class (mean 82.78) compared to the control class (mean 69.41), with a significance value of 0.000. Therefore, the Guided Writing method assisted by picture-sequencing media proved effective in improving the creative writing skills of third-grade elementary school students.